PENGARUH PENGGUNAAN BONEKA TANGAN DALAM MENINGKATKAN KEMAMPUAN MENYIMAK ANAK USIA 5-6 TAHUN DI TKIP NUR ASSALAAM - Julianti, Adliana; Dewi, Rikha Surtika; Hudha A, Nandhini (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
The language development of children aged 5-6 years is characterized by children answering complex questions, naming groups of pictures that have the same sound, communicating verbally, having a vocabulary, and knowing symbols in preparation for reading, writing and arithmetic, constructing simple sentences in a complete structure (main sentence-predicate-adverb), has more words to express ideas to other people, continues a story/fairy tale that has been heard and continues understanding concepts in storybooks. This research aims to determine the effect of hand puppets on ability listening to children aged 5-6 years at TKIP Nur Assalaam. This research uses a quantitative approach with experimental methods. The population in this study was 15 children, the variables in this study were independent and dependent. Data analysis techniques use hypothesis testing or t tests. The results of this research are based on hypothesis test calculations, the results obtained are t table with a significance level of 0.5, namely 1.761 with t calculated, namely 3.162, therefore it can be seen that t0 is greater than tt, namely 3.162 > 1761.